Kebangkitan Kristus Terhadap Dosa Membawa Anugerah Dalam Kehidupan Manusia Berdosa Roma 6 : 10-11 - Darius Kahabi Raumbani; Aprianus Lendrik Moimau (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
Everyone doesn't want something bad to happen in their life. This means that all humans want the best in their lives. Therefore, if people are faced with all the problems in their lives, the word complaining becomes a basic reference in their lives. Feeling that they have no more hope in their lives. It should be noted that such individuals who easily complain when faced with a problem are individuals who have no faith or hope in their lives. In dealing with such individuals, special attention is needed in terms of developing and directing them. If such a person is not directed then don't be mistaken if they are still in the initial position, that is, they are easily carried away and in the end end up doing things that should not be normal. The difference between people who have hope and people who have no hope in their lives is; People who have hope do not easily give up hope in their lives even though the problems they face are very difficult. This is because they still have hope that lifts them from adversity. In contrast, people who have no hope easily give up on circumstances and if the problems they face are too heavy they may choose a shortcut, namely by ending their lives in an unnatural way. Therefore, it is very important in human life to have a solid foundation that is able to provide solutions, even in human helplessness, there are ways to help and lift this downturn.